Real-time tracking of lung tumors using a 1.5T Elekta Unity MR-Linac: first clinical experiences - Smith, Blake; Allen, Bryan; Rusu, Samuel; St-Aubin, Joel; Hyer, Daniel (Frontiers in Oncology, 2025)
There is a growing interest in the application of MRI-guided adaptive radiotherapy (MRIgART) to improve the treatment of lung tumors. Motion management plays a central role to better localize these tumors and minimize toxicities to surrounding healthy tissue. Elekta recently released their comprehensive motion management system for the Unity 1.5T MR-Linac, enabling real-time tracking and predictive gating using MR cine imaging during treatment. We report our first clinical experiences using this gating technology to treat patients with central lung tumors adjacent to critical structures on the Unity MR-Linac using both conventional and SBRT fractionations. A surrogate structure was tracked if the primary target could not be visualized. Beam gating was automatically performed if the system detected the target moving outside of the defined gating envelope, which was set as the planning target volume. Integrating this technology has profoundly impacted our MRIgART program; we have been able to treat challenging lung tumor patients with greater precision and have begun to reduce our PTV margins, leading to improved dose sparing of nearby critical structures.